Globalization and trade liberalization: implications on the feed, grains and livestock industries in Southeast Asia - Suresh A. Chandran (Malaysian Agricultural Research and Development Institute (MARDI), 2022)
In the Southeast Asia regional livestock industry, one topic seems to have taken centre stage, the impact of trade liberalization and globalisation. Although trade liberalization should ideally benefit all parties, it seems that a fair level playing field is not expected. Regional producers fear an influx of foreign farm produce as a result of the agreements made between regional countries under the ASEAN Free Trade Area (AFTA) and the World Trade Organization (WTO), which takes effect in 2003 and 2005 respectively. Opinion is strongly divided about the scale and the type of impact these agreements and trade liberalization will have on Southeast Asia. One thing though is generally agreed; the path towards trade liberalization will be indeed a bumpy ride. So, is there any light at the end of the tunnel?